Benzamil inhibits neuronal and heterologously expressed small conductance Ca2+-activated K+ channels. (1st November 2019) - Castañeda, Marisol Sampedro; Tonini, Raffaella; Richards, Christopher D.; Stocker, Martin; Pedarzani, Paola
Abstract: Small conductance Ca 2+ -activated K + (SK) channels are expressed throughout the soma and dendrites of pyramidal neurons in the neocortex and hippocampal formation, where they participate in the local regulation of membrane excitability and synaptic signals. Through their inter-play with Ca 2+ channels, SK channels regulate Ca 2+ influx triggered by back-propagating action potentials in dendrites. Inhibition of SK channels affects both the amplitude and duration of Ca 2+ transients, but the role of Ca 2+ clearance mechanisms and their link to SK channel activity has not been established. Here we report the effect of the Na + /Ca 2+ exchanger (NCX) inhibitor benzamil on Ca 2+ extrusion and SK channels in the regulation of dendritic Ca 2+ signals. Benzamil increased the duration and amplitude of dendritic Ca 2+ transients elicited by back-propagating action potentials in hippocampal pyramidal neurons. This data is consistent with previous studies with SK channel blockers and suggests that benzamil inhibits SK channels in addition to the Na + /Ca 2+ exchanger. Here we show that indeed both the neuronal SK-mediated IAHP current and the currents mediated by heterologously expressed SK channels were inhibited by benzamil. The inhibition of recombinant SK channels was seen with different K + concentration gradients, and was stronger at negative voltages. The suppression of SK channels by benzamil is consistent with previous findings on the modulation of Ca 2+ signals by SK channels in neurons. We additionally show that benzamil inhibits neuronal voltage-gated calcium currents. The results prompt a careful reassessment of the effects of benzamil on Ca 2+ transients in native systems, given the spectrum of ion channels and exchangers this compound targets within a similar range of concentrations. Highlights: SK channels regulate back-propagating action potential-induced dendritic Ca 2+ influx. Benzamil increases duration and amplitude of hippocampal dendritic Ca 2+ transients. Benzamil inhibits the neuronal SK-mediated IAHP current and recombinant SK channels. Inhibition of recombinant SK channels by benzamil is stronger at negative voltages. The mode of action of benzamil on neuronal Ca 2+ transients must be carefully assessed.